Regulation of glucose transporter-specific mRNA levels in rat adipose cells with fasting and refeeding. Implications for in vivo control of glucose transporter number. - Kahn, B B (J Clin Invest, 1989)
Fasting in the rat is associated with a rapid and progressive decrease in insulin-stimulated glucose transport activity in adipose cells, which is not only restored to normal, but increased transiently to supranormal levels by refeeding. The mechanisms for these changes in glucose transport activity appear to involve alterations in both glucose transporter number and intrinsic activity (glucose turnover number). In this study, we use the human hepatoma Hep G2 glucose transporter complementary DNA clone to examine the molecular basis for these alterations. Extractable RNA per adipose cell is decreased 35% with 3 d of fasting and increased to 182% of control with 6 d of refeeding after 2 d of fasting. This parallels changes in adipose cell intracellular water, so that total RNA/water space remains relatively constant. When the changes in total RNA/cell are taken into account, Northern and slot blot analyses with quantitative densitometry reveal a 36% decrease in specific glucose transporter mRNA level in cells from the fasted rats. The mRNA level in cells from the fasted/refed rats is restored to normal. These observations correlate closely with previous measurements of glucose transporter number in adipose cell membrane fractions using cytochalasin B binding and Western blotting. The levels of specific mRNAs for tubulin and actin on a per cell basis show similar but more dramatic changes and mRNAs encoding several differentiation-dependent adipose cell proteins are also significantly affected. Thus, the levels of mRNA for multiple adipose cell genes are affected by fasting and refeeding. In particular, this demonstrates that in vivo metabolic alterations can influence the level of a glucose transporter mRNA in adipose cells. This may have implications for the regulation of glucose transporter number and glucose transport activity. IMAGES: